A novel variant marking HLA-DP expression levels predicts recovery from hepatitis B virus infection - Thomas, Rasmi; Thio, Chloe L; Apps, Richard; Qi, Ying; Gao, Xiaojiang; Marti, Darlene; Stein, Judy L; Soderberg, Kelly A; Moody, M Anthony; Goedert, James J; Kirk, Gregory D; Hoots, W Keith; et al. (Journal of virology, 2012)
Variants near the HLA-DP gene show the strongest genome-wide association with chronic hepatitis B virus (HBV) infection and HBV recovery/persistence in Asians. To test the effect of the HLA-DP region on outcomes to HBV infection, we sequenced the polymorphic HLA-DPB1 and DPA1 coding exons and the corresponding 3' untranslated regions (3'UTRs) in 662 individuals of European-American and African-American ancestry. The genome-wide association study (GWAS) variant (rs9277535; 550A/G) in the 3'UTR of the HLA-DPB1 gene that associated most significantly with chronic hepatitis B and outcomes to HBV infection in Asians had a marginal effect on HBV recovery in our European- and African-American samples (odds ratio [OR] = 0.39, P = 0.01, combined ethnic groups). However, we identified a novel variant in the HLA-DPB1 3'UTR region, 496A/G (rs9277534), which associated very significantly with HBV recovery in both European and African-American populations (OR = 0.37, P = 0.0001, combined ethnic groups). The 496A/G variant distinguishes the most protective HLA-DPB1 allele (DPB1*04:01) from the most susceptible (DPB1*01:01), whereas 550A/G does not. 496A/G has a stronger effect than any individual HLA-DPB1 or DPA1 allele and any other HLA alleles that showed an association with HBV recovery in our European-American cohort. The 496GG genotype, which confers recessive susceptibility to HBV persistence, also associates in a recessive manner with significantly higher levels of HLA-DP surface protein and transcript level expression in healthy donors, suggesting that differences in expression of HLA-DP may increase the risk of persistent HBV infection.